A COHORT STUDY COMPARING SHOULDER PRIMARY ADHESIVE CAPSULITIS TREATMENT WITH ARTHROSCOPIC CAPSULAR RELEASE, SUBACROMIAL DECOMPRESSION, ROTATOR INTERVAL RELEASE AND MANIPULATION UNDER GENERAL ANESTHESIA - Akash, Anant; Agrawal, Nilesh Kumar; Kumar, Alok (Student’s Journal of Health Research Africa, 2024)
Background In 90% of cases, adhesive capsulitis is manageable using conservative management strategies but it requires optimum surgical intervention if it is not cured with conservative strategies. This study aims to compare the combination of arthroscopic capsular release and rotator interval release and manipulation under general anesthesia. Method A total of 120 patients who did not respond to conservative management strategies were included in this study. They were divided into two groups: 60 patients underwent manipulation under general anesthesia (GA) alone, and the other 60 patients received a combination of arthroscopic capsular release, rotator interval release, and manipulation under GA. Visual Analog Scale (VAS) and the Oxford Shoulder Score (OSS)were recorded before surgery and at follow-ups after one week, one month, three months, and six months. Results Both VAS and OSS declined significantly in both groups. For the manipulation under the GA group, the OSS decreased from 49.8±3.3 to 30±4.4 after six months, while the combination group saw a reduction from 50.1±4.4 to 17.4±3.0 after six months. Similarly, the VAS decreased from 6.65±0.93 to 1.47±0.8 in the manipulation group, and from 7.6±1.0 to 0.29±0.47 in the combination group after six months. The combination procedure showed significantly better outcomes in terms of both pain reduction and improved shoulder function (p<0.001). Conclusion The combination of arthroscopic capsular release, rotator interval release, and manipulation under general anesthesia provides significantly better outcomes than manipulation under general anesthesia alone for adhesive capsulitis, as evidenced by improvements in VAS and OSS over six months. Recommendation Symptoms and stages of adhesive capsulitis should be taken into consideration while selecting the best possible conservative management strategy and surgical intervention.